Особливості розвитку ехінацеї пурпурової (Echinacea purpurea (L.) Moench ) в багатокомпонентних рослинних угрупованнях - Юрченко, І.Т.; Кохан, Т.П.; Купенко, Н.П.; Журавель, Т.А. (Промышленная ботаника, 2004)
Results of investigations of Echinacea purpurea (L.) Moench development peculiarities in modelled multicomponent plant communities are preseted in the article. The investigations have been conducted with the objective of a search for optimum plant communities composition in which this species would be able to reach phytocenotic optimum. It has been determined that Echinacea purpurea growth is positively influenced by leguminous species Medicago sativa L. ‘Veselopodolyanskaya 11‘, Galega officinalis L. in three-specific variant. The content of graminoid species (Agropyron pectinatum (Bieb.) Beauv.) in plant community as competitors for environmental resurses inhibits growth of Echinacea purpurea (L.) Moench plants.